Die Ordnung der Natur. Vorträge zu historischen Gärten und Parks in Schleswig-Holstein - Hering, Rainer (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2009)
The Landesarchiv Schleswig-Holstein opened the Landesgartenschau 2009 in Schleswig with the exhibition "Die Ordnung der Natur. Historical Gardens and Parks in Schleswig-Holstein ". This exhibition was complemented by a series of lectures which met with a great response. The lectures are published in this volume. Thematically, the volume is divided into two parts: The first four contributions deal with historical gardens and parks in Schleswig-Holstein. The second part of the volume points beyond the borders of Schleswig-Holstein. It deals with horticultural schools as vocational training for "higher daughters" in the Empire, gardens and nature in the context of democratically anti-democratic, folk ideology, the importance of gardens and parks in film and gardens in Duckburg.